A Critical Study of Class Ten Our English Book - Shrestha, R.K.P.; Khanal, Ramnath (Journal of Advanced Academic Research, 2017)
A textbook holds an important place in ELT programme, particularly in an EFL setting where most teachers depend totally on the approved books, and don't bother to prepare tailor-made teaching materials. Objectives: The main objective is to critically examine the current English textbook for class ten used by all the government as well as English-medium private schools across Nepal. Methodology: A descriptive qualitative research design was adopted to evaluate the quality of the book on mainly two criteria: what to teach and how to teach, At the same time, many other things have been taken into consideration, for example, what is the quality of the input in the book from the viewpoints of four elements of language and four macro skills as well as their constituent micro skills, what is the learning outcome of the book, and so on. Result: There seems to be serious loopholes in the organization of the presentation and practice materials of the book from both viewpoints: knowledge transmission and communicative ability development. Conclusion: The book needs to be adapted and rewritten.